Association of oestrogen receptor alpha gene polymorphisms with systemic lupus erythematosus risk: An updated meta-analysis. (February 2019) - Xie, Qiao-Mei; Hu, Hua-Qing; Li, Su-Su; Wang, Fang; Zhang, Man; Jiang, Shan-Qun; Pan, Fa-Ming; Su, Hong; Zou, Yan-Feng
Abstract: Background: Systemic lupus erythematosus (SLE) is a complex, chronic autoimmune disease, and oestrogen is considered to be a predisposing factor for SLE. Although some studies are conducted to explore the association between oestrogen receptor alpha (ERα) gene polymorphisms and SLE susceptibility, their results are inconsistent. Methods: Meta-analysis was conducted to confirm whether ERα gene polymorphisms were associated with SLE susceptibility, and the strength of association was anticipated by pooled ORs with 95% CIs. Stata software package version 12.0 was used to calculate all the statistical analyses. Results: Twelve studies included 2494 cases and 4176 controls were incorporated in our meta-analysis. A significant association was found for ERα PvuII polymorphism in the overall population (CC+CT vs TT: OR  = 1.334, 95% CI  = 1.195–1.490, P  < 0.001; CC vs TT: OR  = 1.401, 95% CI  = 1.096–1.791, P  = 0.007; CT vs TT: OR  = 1.284, 95% CI  = 1.141–1.444, P  < 0.001; C vs T: OR  = 1.221, 95% CI  = 1.084–1.375, P  = 0.001), while there was no significant association for ERα XbaI polymorphism. Besides, in stratification analyses by ethnicity, the PvuII polymorphism was associated with an increased risk of SLE in Asians (CC+CT vs TT: OR  = 1.379, 95% CI  = 1.203–1.581, P <  0.001; CT vs TT: OR  = 1.308, 95% CI  = 1.130–1.515, P  < 0.001; C vs T: OR  = 1.240, 95% CI  = 1.052–1.462, P  = 0.010), while for ESR1 XbaI polymorphism, a significantly increased risk of SLE susceptibility was found in Asians (GA vs AA: OR =  1.271, 95% CI  = 1.101–1.467, P  = 0.001). Conclusion: Our meta-analysis indicated that the ERα PvuII polymorphism was significantly associated with SLE susceptibility in the overall and Asian populations, while the ERα XbaI G A genotype only played a key role in SLE susceptibility in Asian populations. Highlights: PvuII polymorphism is a significant risk factor for SLE (under dominant model, homozygous model, heterozygous and allele model). XbaI polymorphism in the heterozygous model is a significant risk factor for SLE in Asians. For ERα polymorphism, SLE risk was significantly affected by ethnicity. Screening for genotype of ERα gene may help identify high-risk populations of SLE.